Population pharmacokinetic model of vancomycin in postoperative neurosurgical patients - Shifeng Wei; Shifeng Wei; Dongjie Zhang; Dongjie Zhang; Zhigang Zhao; Zhigang Zhao; Shenghui Mei; Shenghui Mei (Frontiers Media S.A., 2022)
Objective: Vancomycin is commonly used in postoperative neurosurgical patients for empirical anti-infective treatment due to the low success rate of bacterial culture in cerebrospinal fluid (about 20%) and the high mortality of intracranial infection. At conventional doses, the rate of target achievement for vancomycin trough concentration is low and the pharmacokinetics of vancomycin varies greatly in these patients, which often leads to treatment failure. The objective of this study was to establish a population pharmacokinetic (PPK) model of vancomycin in postoperative neurosurgical patients for precision medicine.Method: A total of 895 vancomycin plasma concentrations from 560 patients (497 postoperative neurosurgical patients) were retrospectively collected. The model was analyzed by nonlinear mixed effects modeling method. One-compartment model and mixed residual model was employed. The influence of covariates on model parameters was tested by forward addition and backward elimination. Goodness-of-fit, bootstrap and visual predictive check were used for model evaluation. Monte Carlo simulations were employed for dosing strategies with AUC24 targets 400-600.Result: Estimated glomerular filtration rate (eGFR), body weight (BW) and mannitol had significant influence on vancomycin clearance (CL). eGFR(mL/min)=144×(Scr/a)b×0.993age, for female, a = 0.7, Scr ≤ 0.7 mg/dl, b = −0.329, Scr > 0.7 mg/dl, b = −1.209; for male, a = 0.9, Scr ≤ 0.9 mg/dl, b = −0.411, Scr > 0.9 mg/dl, b = −1.210. Vancomycin clearance was accelerated when co-medicated with mannitol and increased with eGFR and BW. In the final model, the population typical value is 7.98 L/h for CL and 60.2 L for apparent distribution volume, CL (L/h)=7.98×(eGFR/115.2)0.8×(BW/70)0.3×eA, where A = 0.13 when co-medicated with mannitol, otherwise A = 0. The model is stable and effective, with good predictability.Conclusion: In postoperative neurosurgical patients, a higher dose of vancomycin may be required due to the augmented renal function and the commonly used mannitol, especially in those with high body weight. Our vancomycin PPK model could be used for individualized treatment in postoperative neurosurgical patients.